Acute infusion of levosimendan enhances atrial fibrillation in an experimental whole-heart model. (1st June 2017) - Frommeyer, Gerrit; Kohnke, Anja; Ellermann, Christian; Dechering, Dirk G.; Kochhäuser, Simon; Reinke, Florian; Fehr, Michael; Eckardt, Lars
Abstract: Background: The calcium sensitizer levosimendan is clinically employed in decompensated heart failure. The aim of the present study was to assess effects of levosimendan on atrial electrophysiology in an experimental whole-heart model. Methods and results: 13 rabbit hearts were isolated and Langendorff-perfused. Thereafter, hearts were paced at cycle lengths of 350 ms, 250 ms and 200 ms in the atrium. A standardized protocol employing atrial burst pacing induced atrial fibrillation (AF) in 4 of 13 hearts under baseline conditions (mean: 3.3 ± 2.1 episodes). Subsequently, levosimendan was administered in two concentrations (0.25 μM, 0.5 μM). Two monophasic action potential recordings on the left- and two on the right atrial epicardium displayed a decrease of atrial action potential duration (aAPD, − 27 ms, p < 0.05) and atrial effective refractory period (aERP; − 29 ms, p < 0.05) under the influence of 0.5 μM levosimendan. The described alterations of atrial electrophysiology led to and increased inducibility of AF. Of note, treatment with 0.25 μM levosimendan resulted in induction of AF in 11 of 13 hearts (mean: 8.9 ± 3.5 episodes). Under the influence of 0.5 μM levosimendan 12 of 13 hearts were inducible (mean: 9.8 ± 3.8 episodes). Conclusion: In the present study acute infusion of levosimendan in isolated rabbit hearts resulted in an abbreviation of atrial action potential duration and a reduction of aERP. This led to a significantly elevated inducibility of atrial fibrillation. These results suggest a proarrhythmic effect of levosimendan regarding atrial fibrillation. This aspect should be further investigated in the clinical setting. Highlights: Levosimendan reduces atrial action potential duration and refractory period. Levosimendan thereby enhances occurrence of atrial fibrillation. These experimental results deliver the electrophysiologic explanation for similar findings in clinical studies.